Multiple sclerosis treatment: a future that begins today - Drulović, Jelena (Archives of Pharmacy, 2022)
Multiple sclerosis (MS) is an incurable chronic inflammatory and neurodegenerative disorder of the central nervous system (CNS). It is the leading cause of the non-traumatic disability in young and middle-aged individuals, which affects 2.8 million people worldwide. The therapeutic strategy in MS should be to minimize number of relapses and lesions on brain and spinal cord MRI, disability progression and brain atrophy, at all stages of the disease. It has to be emphasized that this is especially important in the early phase of the disease, when it is possible to reduce the development of new lesions and amount of brain inflammation, which lead to both, the long-term disability progression and atrophy. Increasing number of various disease-modifying therapies (DMTs) has been approved for the treatment of relapsing forms of MS, and rather recently, only one for the treatment of primary progressive MS and one for the treatment of secondary progressive MS. These drugs can directly influence the disease course, by reducing relapses, slowing disability progression, reducing the number of new lesions and slowing the rate of brain atrophy. Adequate lifestyle interventions, along with early initiation of the treatment with DMTs that reduce disease activity and consideration of switching to alternative therapy, if monitoring shows suboptimal response, are key points of this strategy. Diagnosis is today established 10-fold more rapid than in 1980s and substantial evidence now implicates that early treatment is significantly more effective than late treatment.